2022
DOI: 10.1044/2021_ajslp-21-00249
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Burden in Caregivers of Adults With Dysphagia: A Systematic Review

Abstract: Introduction: A previous review suggested that dysphagia is negatively associated with burden in caregivers of community-dwelling older adults. Other literature suggests similar patterns of burden may be found across adult patient populations. The current study, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, was conducted to determine the impact of dysphagia on caregivers of adults, regardless of etiology. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The present results showed that texture‐modified food was significantly related to a higher caregiver burden. Previous studies showed that the caregiver burden related to dysphagia is related to the preparation of appropriate meals and concerns about aspiration 13 . Our study showed that caregivers in the texture‐modified food group were similarly careful about proper meal preparation, aspiration and choking; furthermore, they had a higher number of daily attention points than the tube‐feeding and normal group.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…The present results showed that texture‐modified food was significantly related to a higher caregiver burden. Previous studies showed that the caregiver burden related to dysphagia is related to the preparation of appropriate meals and concerns about aspiration 13 . Our study showed that caregivers in the texture‐modified food group were similarly careful about proper meal preparation, aspiration and choking; furthermore, they had a higher number of daily attention points than the tube‐feeding and normal group.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies showed that the caregiver burden related to dysphagia is related to the preparation of appropriate meals and concerns about aspiration. 13 Our study showed that caregivers in the texture-modified food group were similarly careful about proper meal preparation, aspiration and choking; furthermore, they had a higher number of daily attention points than the tube-feeding and normal group. Regarding daily meals, fears about aspiration and choking, which are directly related to adverse health events, imposed an emotional burden on caregivers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations